Pengembangan Ecolearn (Economic Learning) Sebagai Sumber Belajar Berbasis Situs pada Pembelajaran Ekonomi - Ni'matul Istiqomah; Ainun Diesta Fidinnia (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Economic learning that adapts to technological advances and be packaged as digital media needs to be applied to today's learning systems to make it easier, practical and flexible. That is how students need ecolearn as a medium as well as a innovation learning resource. Economics learning applied in SMA Lab UM has not been varied and tends to be conventional, so students have difficulty understanding the material. Students need learning resources that are much more adaptive to technological advances. Students need ecolearn as a learning resource. The purpose of this research is to produce site-based learning resources for Economics subjects at SMA Laboratorium UM Malang and to test the feasibility of site-based learning resources according to media experts and material experts. The research design adapts from Borg and Gall by planning, developing, validating and disseminating products. Then, data analysis using the percentage descriptive method, which converts quantitative data in the form of numbers into percentages to then be explained in a concluding paragraph exposure. Based on validation from material experts, this media has a score of 80.5%. This media has a validation score of 98.66% with very valid criteria or very feasible to use. By the score, this media is classified as a very valid or very feasible criteria. Then, ecolearn was tested to SMA Lab UM to get responses from students. Based on student responses as users, this media gets a score of 86.58% and also classfied as a very valid or very feasible criteria. Therefore, based on the results of validation and exposure to user responses, ecolearn is feasible to be used in learning Economics in schools. Ecolearn media can also be used as a complement in distance learning. Teachers and students are very interested in the ecolearn as site-based learning media because this media is able to increase students' motivation to learn and students' sense of curiosity towards learning economics.